Sintesis dan Karakterisasi Fotokatalis TiO2/Cu dengan Metode yang Ramah Lingkungan - Rahmi, Zulfiyanti; Suryani, Okta (Departemen Kimia FMIPA UNP, 2024)
Most of the energy consumed comes from non-renewable fossil fuel resources. Therefore, a renewable and environmentally friendly energy source is needed, namely sunlight. One way to utilize sunlight is to store it into chemical compounds, namely hydrogen. The hydrogen used comes from water through a process of decomposing its molecules called water decomposition. Water decomposition uses sunlight and semiconductor photocatalysts, such as TiO2. In this study, TiO2 has been synthesized and doped with Cu metal to reduce the band gap with a simple and environmentally friendly method. XRD characterization to determine the structure and particle size. TiO2 has an anatase crystal structure with an average particle size of 28.28 nm. TiO2 has an energy band gap of 3.2 eV. Then doping with Cu metal with varying concentrations of Cu metal soluble (0.1 M san 0.5 M) causes the energy band gap to decrease to 3.17 and 3.07 eV. Metal doping is proven to reduce the band gap energy of TiO2 photocatalysts. In addition, metal doping also helps widen the light absorption area by TiO2, but the absorption is still in the UV region.